Clinical and Patient-Reported Outcomes Following Peroneus Brevis Reconstruction With Hamstring Tendon Autograft. (November 2021) - Chrea, Bopha; Eble, Stephanie K.; Day, Jonathan; Hansen, Oliver B.; Ellis, Scott J.; O'Malley, Martin J.; Drakos, Mark C.
Background: Peroneal tendon injuries are a common cause of lateral ankle pain and instability. While the use of hamstring autograft has been proposed as a viable surgical option for peroneus brevis reconstruction, reported outcomes with this technique are limited in the literature. We present patient-reported and clinical outcomes for patients who underwent peroneus brevis reconstruction with hamstring autograft. Methods: Thirty-one patients were retrospectively identified who underwent a procedure including peroneus brevis reconstruction with hamstring autograft for peroneal tendinopathy between February 2016 and May 2019. All patients who had a peroneus brevis reconstruction were included, and all concomitant procedures were noted. Patient-Reported Outcomes Measurement Information System (PROMIS) surveys were prospectively collected preoperatively and at a minimum of 1 year postoperatively (mean, 24.3; range, 12-52.7) months. Retrospective chart review was performed to evaluate the incidence of postoperative complications and reoperations. Results: When evaluating pre- and postoperative patient-reported outcome surveys (n = 26; 84%), on average, patients reported improvement in every PROMIS domain evaluated, with significant improvement in Physical Function (+5.99; P = .006), Pain Interference (–8.11; P < .001), Pain Intensity (–9.02; P < .001), and Global Physical Health (+7.29; P = .001). Three patients reported persistent pain at a minimum of 1 year postoperatively, of whom 2 required reoperation. No patient reported persistent pain or discomfort at the harvest site of the hamstring autograft. Conclusion: Patients undergoing peroneus brevis reconstruction with hamstring autograft experienced clinically significant improvement in patient-reported and clinical outcomes. Few postoperative complications were observed, and patients reported improvements across all patient-reported outcome domains, with significant improvements for pain and function domains. Reconstruction with hamstring autograft represents a viable surgical option in the setting of peroneal tendinitis or tears. Level of Evidence: Level IV, case series.